2016
DOI: 10.1016/j.rmclc.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Sindrome De Ovario Poliquístico en Mujeres Portadoras De Sindrome Metabólico

Abstract: Introduction:The link between metabolic syndrome and PCOS is given by the pathophysiology characterized by insulin resistance with compensatory hyperinsulinemia. The aim of the study was to determine the prevalence of PCOS in women diagnosed with metabolic syndrome and determination of the components of the latter. Methods: Cross-sectional study in women 18 to 40 years, carriers of metabolic syndrome who were determined glucose, cholesterol and triglycerides; blood pressure, body mass index (BMI), and pelvic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
1
0
5
Order By: Relevance
“…Although in the study this prevalence is maintained, an increase could be observed when the cut-off point that defines abdominal obesity decreases, thus improving sensitivity, but worsening the specificity, by diagnosing people who eventually do not have metabolic syndrome. However, it was found that hyperglycemia is higher in men due to not complying with any type of diet or physical exercise regime which leads to an increase in body index, where it is common to find these elements increased in women over 55 especially with menopause with polycystic ovarian syndrome (Tovar & Celemin, 2016;Pulido et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the study this prevalence is maintained, an increase could be observed when the cut-off point that defines abdominal obesity decreases, thus improving sensitivity, but worsening the specificity, by diagnosing people who eventually do not have metabolic syndrome. However, it was found that hyperglycemia is higher in men due to not complying with any type of diet or physical exercise regime which leads to an increase in body index, where it is common to find these elements increased in women over 55 especially with menopause with polycystic ovarian syndrome (Tovar & Celemin, 2016;Pulido et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha establecido, según la metodología, que, si la paciente cumple con dos de estos tres criterios, entonces es diagnosticada con presencia de SOP. [11][12][13] Se utilizaron los datos de peso y talla presentes en los registros médicos y se determinó el índice de masa corporal, para ello se empleó la expresión matemática estandarizada: IMC= peso (kg)/talla(m 2 ) [14][15][16] . Clasificando a las pacientes en normopeso (18.5-24.9), sobrepeso (25-29.9), obesidad grado I (30-34.9), obesidad grado II (35-39.9) y obesidad grado III (≥40).…”
Section: Materials Y Métodosunclassified
“…Después de confirmar el diagnóstico, se debe de realizar une evaluación adicional, que permita descartar la presencia de enfermedades metabólicas. Se observó en un estudio realizado, que e438 el 29.2% de las mujeres con SOP, presentan síndrome metabólico (12). Es recomendado tamizar a estas mujeres por resistencia a la insulina y diabetes mellitus tipo 2, debido a que el SOP es un factor de riesgo para el desarrollo de esta enfermedad.…”
Section: Enfermedades Asociados a Sindrome De Ovario Poliquisticounclassified